Mutant Gq/11 promote uveal melanoma tumorigenesis by activating YAP - Yu, Fa-Xing (2014)
Uveal melanoma (UM) is the most common cancer in adult eyes. Approximately eighty percent of UMs harbor somatic activating mutations in GNAQ or GNA11 (encodes Gq or G11 respectively). Herein, we show in both cell culture and human tumors that cancer-associated Gq/11 mutants activate YAP, a major effector of the Hippo tumor suppressor pathway that is also regulated by G-protein coupled receptor (GPCR) signaling. YAP mediates the oncogenic activity of mutant Gq/11 in UM development, and the YAP inhibitor verteporfin blocks tumor growth of UM cells containing Gq/11 mutations. This study reveals an essential role of the Hippo-YAP pathway in Gq/11-induced tumorigenesis and suggests YAP as a potential drug target for UM patients carrying mutations in GNAQ or GNA11.